2018
DOI: 10.1148/radiol.2018170757
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Patient-specific Dose to the Thyroid and Breasts and Overall Risk in Chest CT When Using Organ-based Tube Current Modulation

Abstract: Purpose To assess the potential dose reduction to the thyroid and breasts in chest computed tomography (CT) with organ-based tube current modulation (OBTCM). Materials and Methods In this retrospective study (from January 2015 to December 2016), the location of the breasts with respect to the reduced tube current zone was determined. With Monte Carlo simulations, patient-specific dose distributions of chest CT scans were calculated for 50 female patients (mean age, 53.7 years ± 17.5; range, 20-80 years). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Finally Wang et al found a dose reduction of 34–39% for the risk organ–based tube current modulation using a semianthropomorphic phantom [ 21 ]. Our results are in line with those studies, but there has been a recent study by Franck et al that showed there is only a 9% dose reduction in the female breast, in contrast to our results [ 22 ]. This difference can be explained in that, in their study, not all breast tissue was within the reduced tube current zone, and therefore the effect was not as big as if the breast tissue was within the reduced tube current zone.…”
Section: Discussionsupporting
confidence: 93%
“…Finally Wang et al found a dose reduction of 34–39% for the risk organ–based tube current modulation using a semianthropomorphic phantom [ 21 ]. Our results are in line with those studies, but there has been a recent study by Franck et al that showed there is only a 9% dose reduction in the female breast, in contrast to our results [ 22 ]. This difference can be explained in that, in their study, not all breast tissue was within the reduced tube current zone, and therefore the effect was not as big as if the breast tissue was within the reduced tube current zone.…”
Section: Discussionsupporting
confidence: 93%
“…Although this approach has been documented to reduce dose to superficial radiosensitive organs, it provokes a dose increase to centrally and posteriorly located organs. Franck et al [6] have shown that OTCM in thorax CT of females reduces the dose to thyroid and breast by 18% and 19%, respectively. However, the doses for lung, liver, and kidney were found 17%, 11%, and 26% higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach has been documented to deliver images of increased noise [10,11]. Previous studies performed in adult patients have shown that OTCM may substantially reduce radiation dose to superficial radiosensitive organs [6,8,12,13]. To our knowledge, there is scarce published data on the effect of OTCM on radiation dose to superficial radiosensitive organs and image quality in pediatric CT examinations [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies evaluated the influence of medical radiation exposure on future occurrence of malignant tumors in women who were exposed to high radiation doses due to multiple radiation examinations or treatment by radiotherapy. [ 14 16 ] However, the advantages of lung CT examination in revealing small pulmonary lesions has gradually become an important tool in physical examinations. In the conventional chest CT scanning procedure, the direct exposure of the breast to radiation is not avoidable, and the breast is not the target organ in lung CT screening; therefore, it is self-evident that the biological effect of frequent examinations or large doses of radiation might be a potential cancer risk.…”
Section: Discussionmentioning
confidence: 99%